(untitled) (Research, Society and Development, 2022)
The study aims to identify the scientific production and articles guided by the Theory of Social Representations, about the elderly in the period of the pandemic caused by Covid-19. The sample consisted of 11 articles, produced with the theme, and these were analyzed by the Iramuteq software, using the Reinert Method, from the Descending Hierarchical Classification (CHD) and the Similarity Analysis (SA). The results of the lexical analysis of the corpus presented five classes: Emotional aspects of Covid-19 disease; Conceptions about the origin of the coronavirus; Role of the media in the construction of Covid-19’s social representation; Identification of initial studies on coronaviruses; and, Adaptations to the constraints and challenges of the Covid-19 pandemic. In the similarity analysis, Covid-19 and social representation were related to the words elderly, coronavirus, study, identification. And those with low co-occurrences aimed at experience, illness, fear, strategy, indicating the representative psychosocial aspects of getting sick. Fear was the figurative element of objectification, anchored in psycho-emotional factors, as it was associated not only with the risk of contagion, but also with the risk of death. For the elderly, the adverse feelings and the consequences of isolation were felt by two aspects, the first with the spread of the dangerous virus for the elderly, that brought uncertainties about the future and generate psychosocial implications not yet measured in the long term.